Burnout in microvascular reconstructive otolaryngology – head and neck surgeons: Potential modifiable workplace factors. Issue 11 (30th August 2021) - Kejner, Alexandra E.; Patel, Rusha; McMullen, Caitlin; Sykes, Kevin J.; Shnayder, Yelizaveta
Abstract: Background: Burnout has been previously assessed in head and neck microvascular reconstructive surgeons (HNMVS), but not in the context of modifiable workplace factors. Methods: Anonymous, cross‐sectional survey. The Abbreviated Maslach Burnout Inventory – Human Services Survey for Medical Personnel (aMBI‐HSS) was utilized to assess emotional exhaustion (EE), depersonalization (DP), and personal achievement (PA). Modifiable risk factors were also evaluated. Results: High risk of burnout by EE, DP, and PA was demonstrated in 24%, 9%, and 27% of respondents, respectively. EE was associated with <10% dedicated research time, lack of autonomy over clinic schedule, inadequate inpatient support, and lack of supportive clinical partner. DP was associated with >3 operative days, difficulty balancing academic commitments, and lack of supportive clinical partner. Dedicated research time and two or fewer days of block time were protective. Conclusions: Burnout was associated with several modifiable workplace factors. Addressing these may prevent moderate to severe burnout in HNMVS.